O drama do médico no encontro com o paciente nos cenários dos serviços de saúde público e privado - Vasques, Karine Bessa Porto Pinheiro (2016)
10 ABSTRACT In recent decades, Brazil has been the scene of major political, economic, demographic and social transformations. This democratization process also includes the reform of the Brazilian health sector, which establishes the public and private health services. Health services are now offered by individuals with regulated professions or specific training and can be provided in offices, homes, public spaces, clinics, health centers and hospitals. The aim of the present research is to understand the perception of doctors – who hold similar and concurrent professional activities in the public and private sectors – regarding the interaction between doctors and patients in the practice setting. We are anchored to the ever-watchful eye on the dynamics and peculiarities of health services in order to: identify how the medical character has been constructed from the respondents’ point of view; unveil the performance of their social role; describe doctors’ feelings regarding their professional practice; analyze the perception of doctors regarding the audiences and performance settings. This is a qualitative study conducted in the light of the conception of Goffman’s theatrical representation of dramaturgy and Symbolic Interaction. In this perspective, each one plays a role and interacts with others through verbal and physical behaviors, using the appearance and performance to convince the other of one’s own activities. When the individual is in contact with someone else, s/he is representing and benefiting from a dramaturgical practice. The 10 doctors who participated in the study were determined by intentional non-probability sampling; however, they should hold similar and concurrent professional activities in public and private services and provide care to patients in a direct and personal way. The number of respondents was defined by theoretical saturation of data, that is, when the conceptual understanding of research questions was deepened during the collection of stories and analysis. Data were collected from November 2015 to December 2015 through open interviews and the story-and- drawing procedure. During the interviews, the respondents were asked to draw the image they had about the trigger phrase "Because in the office, they are my clients, they pay me to care for them, right? And at the Cancer Prevention Institute, they are my patients, right?". Data were organized in themes that were analyzed based on the theoretical background. The results showed that the 10 doctors worked in public and private services in the areas of clinical oncology, general clinical, surgical oncology, radiation therapy, mastology, gynecology and obstetrics; they were aged 32-71 years old and were mostly men (06). All of them held a least a specialization/medical residency degree. The identification of codenames was chosen by the participants, who decided which character best described them. The themes addressed the construction and performance of the medical character in different situations and settings; the social construction of the medical character; the mask under which the professional is hidden; feelings experienced by the doctor; academic training for medical performance in different practice settings; the doctors’ view of the circumstantial role of patients in public and private settings; physical and structural setting and access to materials and medicine procedures; organizational climate and organization of processes; productivity in relation to time, production and pay; the time available for each person; the influence of the presence of other characters in scenes on the performance of the actors. They recognized the interview using the Drawing-trigger (an unfolding of the Trinca drawing-story, developed by the author) procedure as an encouraging tool for understanding the relationship with the patient. The doctor-patient relationships require attention to the peculiarities of the sector in which it takes place, for the contributions resulting from it should be continuous and interdependent. It is concluded that there are consistencies and differences in the doctor-patient relationship in the two sectors studied. The similarities lie in the treatment given to the patients themselves, not differentiating the place where they are receiving care; and the differences are driven by structural and organizational settings of the public and private sector, but with remaining similarities in the diffusion of moral and ethical values.